К вопросу синтеза схем гидропневмоагрегатов - Полушкин, К. А. (НТУ "ХПИ", 2012)
Описывается разработанный автором алгоритм безраздельной декомпозиции уравнения по двум переменным с выбором рациональной схемы разложения. Алгоритм разрешает исключить перебор схемных решений и избрать наиболее приемлемую схему только по виду остаточных функций, который можно получить вследствие разложения данной функции за формулой Шеннона. Применение алгоритма продемонстрирован на конкретном примере.

The algorithm of undivided decomposition of equations by two variables with the choice of the rational scheme of decomposition developed by the author is described. The algorithm allows to eliminate the surplus of scheme decisions and choose the most acceptable scheme only according to the form of remaining functions that can be got as a result of decomposition of this function after the Shannon’s formula. Application of the algorithm is shown on the concrete example.
To the question of synthesis of schemes of hydropneumoaggregates
Keywords: разложение; синтез; алгоритм